The Antioxidative Properties of Selected Herbs Estimated Using Various Assays - Bronisław K. Głód; Mateusz Borkowski (Journal of Chemistry)
Antioxidants can be determined using a variety of analytical assays. The total of antioxidant properties, depending on the sum of the products of their concentrations and antioxidant powers in the sample, is usually called total antioxidant potential (TAP). The direct method developed by us, based on the voltammetric measurements, was used to determine the TAPs of selected herbs. However, it is expected that the detection limit of this assay will be much lower when the convection current is increased and the capacitive current is eliminated. Such conditions are found in electrochemical HPLC detection. The advantage of this method is the ability to perform measurements at different potentials, which is analogous to the measurements related to various radicals in indirect methods. Measurements performed at high potentials of the working electrode allow us to test weak antioxidants. It turned out that electrochemical methods provided additional information about the antioxidant properties of the herbs. Some of them have a large part of TAP caused by weak antioxidants in high concentrations. The obtained results were correlated with the TAP values related to DPPH (2, 2-diphenyl-1-picrylhydrazyl) radicals and the total content of polyphenols in the sample.